Photosynthetic Responses of The Red Seaweed Gracilaria fisheri to Green and Brown Seaweed Extracts - Numuean, Nittiya; Kaewduang, Boonanan; Praiboon, Jantana; Ruangchuay, Rapeeporn; Chirapart, Anong (Journal of Fisheries and Environment, 2024)
Seaweed extracts are widely used as biostimulants in crops for promoting growth and stress resistance. This study examined the photosynthetic responses of Gracilaria fisheri to extracts of green seaweeds Chaetomorpha crassa (Ch-SE) and Rhizoclonium riparium (Rhi-SE), and brown seaweeds Padina sp. (Pad-SE) and Sargassum oligocystum (Sar-SE). Thalli of G. fisheri were treated with varying concentrations of the extracts (0, 1, 2, 3, 4, and 5 g SE×L-1) under controlled conditions: salinity of 30‰, temperature of 25–26 °C and light intensity of 200 µmol photons×m-2×s-1. Photosynthesis was measured using a dissolved oxygen sensor and pulse amplitude-modulated fluorometry. Results showed that light intensity rapidly increased with irradiance up to 625 mmol photon×m-2×s-1 without photoinhibition in the SE-treated algae, unlike the control. The electron transport rate (ETR) of the SE-treated algae significantly increased compared to the control at 625 mmol photon×m-2×s-1. Net photosynthesis (Pnet) of the SE-treated G. fisheri was two- to fivefold higher than the control. Additionally, the maximum quantum yield also increased in SE-treated algae, with the highest increase in Rhi-SE treatment, followed by Pad-SE, Ch-SE, and Sar-SE treatments. This study suggests that green and brown seaweed extracts effectively enhance photosynthesis in G. fisheri.